Proteomic analysis of the mandibular glands from the Chinese crocodile lizard, Shinisaurus crocodilurus – Another venomous lizard?. (15th March 2023) - Calvete, Juan J.; Lomonte, Bruno; Lorente, Carolina; Pla, Davinia; Zollweg, Michael; Mebs, Dietrich
Abstract: Based on its phylogenetic relationship to monitor lizards (Varanidae), Gila monsters (Heloderma spp.), and the earless monitor Lanthanotus borneesis, the Chinese crocodile lizard, Shinisaurus crocodilurus, has been assigned to the Toxicofera clade, which comprises venomous reptiles. However, no data about composition and biological activities of its oral secretion have been reported. In the present study, a proteomic analysis of the mandibular gland of S. crocodilurus and, for comparison, of the herbivorous Solomon Island skink Corucia zebrata, was performed. Scanning electron microscopy (SEM) of the teeth from S. crocodilurus revealed a sharp ridge on the anterior surface, but no grooves, whereas those of C. zebrata possess a flattened crown with a pointed cusp. Proteomic analysis of their gland extracts provided no evidence of venom-derived peptides or proteins, strongly supporting the non-venomous character of these lizards. Data are available via ProteomeXchange with identifier PXD039424. Graphical abstract: Image 1 Highlights: A proteomic analysis of the mandibular glands of Shinisaurius crocodilurus and Corucia zebrata, was performed. Scanning electron microscopy of S. crocodilurus' teeth revealed a sharp ridge on the anterior surface, but no grooves. Scanning electron microscopy of C. zebrata teeth showed a flattened crown with a pointed cusp. Proteomic analysis of gland extracts of S. crocodilurus and C. zebrata showed absence of venom-derived peptides or proteins. Our results strongly support the non-venomous character of both S. crocodilurus and C. zebrata.